MEASURING POSITIONING “NUSANTARA” : BRAND ANALYSIS OF EAST KALIMANTAN AS NEW CAPITAL CITY OF INDONESIA - Vivi Varlina; Netti Anjelina (Jurnal Komunikasi & Media Digital, 2023)
The relocation of the capital city of Indonesia from Jakarta to East Kalimantan has always attracted attention. Although this has been decided through a long democratic process, this relocation still brings pros and cons in society. Within the framework of economic transformation, realizing prosperity and equitable development, the Government of Indonesia is moved to answer this challenge. However, does this relocate have any urgency, especially since Indonesia has just recovered from the impact of the Covid-19 pandemic? Then how about building a new modern capital city with complete facilities, but still preserving nature and the environment? This research was conducted using a descriptive quantitative approach. Conceptualization is emphasized on the positioning and branding of East Kalimantan by referring to current conditions, as well as the utilization of existing resources in order to reach the ideal condition of the capital city. In this context, the government public relations has a strategic role in measuring people's aspirations, as well as campaigning for a city branding blueprint for the new capital city.